Pembelajaran Alquran melalui metode Tilawati untuk anak usia dini di Taman Pendidikan Al-Qur'an - mutia ramadhani; Dinda Nabila; Dzakira Naura; Sutrimo (Liberi, 2026)
This study aims to determine the application of the Tilawati method in Quranic learning for early childhood at the Baitul Hikmah Islamic Boarding School (TPQ). The Tilawati method is a Quranic learning method that combines classical and individual approaches, using songs (rost) to increase children's interest in learning. This study used a qualitative approach, with data collection techniques through interviews, observation, and documentation. The results indicate that the implementation of the Tilawati method at TPQ Baitul Hikmah is effective and able to improve the Quranic reading skills of early childhood children. This is supported by a structured learning system, the use of varied media, and routine activities such as memorizing prayers and short surahs. Furthermore, the Tilawati method is considered more effective than previous methods because it creates a fun and engaging learning environment for children.However, several obstacles remain in its implementation, such as differences in ability between children and the need to improve teacher skills. Therefore, efforts to develop methods and provide training for educators are needed to optimize learning.